Immunohistochemical Study on Hormone Receptors and HER2 Status in Invasive Breast Carcinoma and its Therapeutic Implications - Karim, Md Iqbal; Islam, Md Tarikul; Nargis, Nazlima (Bangladesh Critical Care Journal, 2019)
Background: Immunohistochemistry (IHC) has become an integral part of histopathology in the diagnosis of biopsysample. Although haematoxylin and eosin (H & E) stain remains the fundamental basis for diagnostic pathology of thebreast, IHC stains provide useful and sometimes vital information. Moreover, the role of hormonal therapy in hormonereceptor–positive breast tumours, as well as targeted chemotherapeutic agents for human epidermal growth factorreceptor-2 (HER2) positive cases, IHC studies represent a major part of workups. Objective: The study was carried out to identify the common immunohistochemical markers in invasive breastcarcinoma and to find out the relationship between hormonal receptor status and HER2 over expression with the gradeof tumour and its therapeutic implications. Method: In the present study, immunohistochemical assay of total seventy-two blocks of breast carcinoma patients wasperformed to know the hormone receptors and HER2 status as well as histological examination. Result: 72 samples were grouped to study hormonal status and their relation with clinicopathological factors. Outcomeof this study documented 58.33 %, 44.44% and 25 % expression rate of estrogen receptor (ER), progesterone receptor(PR) and human epidermal growth factor receptor-2 (HER2) respectively. The negative expression of HER2 receptorsfound higher (75%) than ER & PR. The ER, PR negative and HER2 Positive cases found in high grade breast cancer(Grade-3). An inverse correlation of HER2 expression with ER and PR expression was observed (p=0.001). Conclusion: The role of hormone receptors and HER2 repression as a prognostic and therapeutic tool in breast canceris widely accepted and effective for patients. Bangladesh Crit Care J September 2019; 7(2): 95-98